Outcomes after hand and upper extremity transplantation - Shores, Jaimie T.; Malek, Veronika (Journal of materials science, 2017)
Hand and upper extremity transplantation (HUET) has emerged as the most frequently performed reconstructive procedure in the burgeoning field of vascularized composite allotransplantation (VCA). VCA refers to a form of transplant with multiple tissue types that represents a viable treatment option for devastating injuries where conventional reconstruction would be unable to restore form and function. As hand transplantation becomes increasingly more common, discussions on advantages and disadvantages of the procedure seem to intensify. Despite encouraging functional outcomes, current immunosuppressive regimens with their deleterious side-effect profile remain a major concern for a life-changing but not life-saving type of transplant. In addition, a growing number of recipients with progressively longer follow-up prompt the need to investigate potential long-term sequelae, such as chronic rejection. This review will discuss the current state of HUET, summarizing outcome data on graft survival, motor and sensory function, as well as immunosuppressive treatment. The implications of these findings for VCA in terms of achievements and challenges ahead will then be discussed.